CODE-MIXING IN LANGUAGE STYLE OF SOUTH JAKARTA COMMUNITY INDONESIA - Jimmi jimmi; Rafelia Elsa Davistasya (Premise: Journal of English Education and Applied Linguistics, 2019)
The purpose of this paper is about to investigate of Code-Mixing appeared in South Jakarta Community while this community having chat each other through social media, WhatsApp and Twitter. The phenomenon of Code-Mixing and Code-Switching in Indonesia became viral in last September. The used of code-mixing helps them to communicate with others, because not all the people can use the language properly. So that, learning about language is really needed. It will increase their vocabularies whether in Bahasa or English. Also, there are few reasons why the community applies the code-mixing in the daily activities. The writer uses the method of qualitative-description research which is done by the writer by getting involved in the community of social media,  having the library and internet research with the relevant sources, and collects the data to be analyzed also describes by explaining the result of the research. The conclusion of the research is by the often using of Code-Mixing, the people indirectly increase their vocabularies. This phenomenon influenced many people to start to apply the Code-Mixing